2018
DOI: 10.1080/13691058.2018.1502472
|View full text |Cite
|
Sign up to set email alerts
|

From sameness to difference: Swedish Somalis’ post-migration perceptions of the circumcision of girls and boys

Abstract: In every society where non-therapeutic female circumcision (FC) occurs, so too does non-therapeutic male circumcision (MC). In the past few decades, the norm in Euro-American societies has been to distinguish between the practices: FC is banned, while MC is condoned or encouraged. We explored Somalis' post-migration perceptions of FC and MC, while considering that they once lived in a society where both practices were widely accepted and now live in a society where there is a legal ban on FC alongside acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…A recent qualitative study on perceptions of MC and FGC in another diasporic context – that of Somali-Swedes – found that ‘MC was perceived as an unquestionably required practice, but FC was viewed as a practice that can be adapted or abandoned’ (Wahlberg et al., 2018: 619). Their finding echoes a sense of differentiation of MC and FGC which is also reflected in much public discourse and academic scholarship.…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study on perceptions of MC and FGC in another diasporic context – that of Somali-Swedes – found that ‘MC was perceived as an unquestionably required practice, but FC was viewed as a practice that can be adapted or abandoned’ (Wahlberg et al., 2018: 619). Their finding echoes a sense of differentiation of MC and FGC which is also reflected in much public discourse and academic scholarship.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with earlier studies in Sweden and Norway. 22,38 However, in a recent study among Kurdish-Norwegians this differentiation between the practices was not as evident, describing a renegotiation of the potential harm a boy may be exposed to with some informants stating they regretted or will refrain from circumcising their boys as they perceive MGC as painful. 33 The Norwegian government's 40 In addition, social pressure and fear of having one's masculinity questioned can make a man ignore his complaints.…”
Section: Factors Associated With the Attitude That Fgc Is Comparablmentioning
confidence: 99%
“…In Sweden, Somali immigrants have been found to largely oppose FGC, with the proportion of opponents increasing with years spent in Sweden 21 . However, in a qualitative study among Swedish Somalis the same development of decreased support towards MGC was not seen 22 …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Även i tidigare svenska studier av attityder till könsstympning har det varit gruppen svensksomalier som utgjort de huvudsakliga informanterna, men i dessa studier har materialet främst insamlats via intervjuer och observationer, inte genom fokusgruppdiskussioner (Johnsdotter 2002(Johnsdotter , 2003(Johnsdotter , 2010(Johnsdotter , 2018Essén & Johnsdotter 2004a, 2004bWahlberg, Johnsdotter, Ekholm m.fl. 2017;Wahlberg, Essén & Johnsdotter 2019).…”
Section: Materialinsamling Och Metodunclassified